2017
DOI: 10.3389/fimmu.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

NR4A Receptors Differentially Regulate NF-κB Signaling in Myeloid Cells

Abstract: Dysregulation of inflammatory responses is a hallmark of multiple diseases such as atherosclerosis and rheumatoid arthritis. As constitutively active transcription factors, NR4A nuclear receptors function to control the magnitude of inflammatory responses and in chronic inflammatory disease can be protective or pathogenic. Within this study, we demonstrate that TLR4 stimulation using the endotoxin lipopolysaccharide (LPS) rapidly enhances NR4A1–3 expression in human and murine, primary and immortalized myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 40 publications
8
37
0
Order By: Relevance
“…The cytoplasmic fractions were separated by SDS-PAGE and transferred onto a polyvinylidenedifluoride membrane (Amersham Biosciences, Little Chalfont, UK). Immunoblotting was performed using antibodies against phospho-NF-κB p65 (1:1,000, Cell Signaling, Boston, MA, USA) or NF-κB p65 (1:1,000, Cell Signaling) ( 31 ). β-actin (1:1,000, Santa Cruz, Dallas, TX, USA) and LaminB1 (1:1,000, Santa Cruz, Dallas, TX, USA) were used as controls ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoplasmic fractions were separated by SDS-PAGE and transferred onto a polyvinylidenedifluoride membrane (Amersham Biosciences, Little Chalfont, UK). Immunoblotting was performed using antibodies against phospho-NF-κB p65 (1:1,000, Cell Signaling, Boston, MA, USA) or NF-κB p65 (1:1,000, Cell Signaling) ( 31 ). β-actin (1:1,000, Santa Cruz, Dallas, TX, USA) and LaminB1 (1:1,000, Santa Cruz, Dallas, TX, USA) were used as controls ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were washed in PBS and lysed in Passive Lysis Buffer (Promega, Madison, WI, USA). The Dual-Luciferase reporter assay system (Promega) was used to quantitate both reporter genes by a POLARstar Omega multimode microplate spectrophotometer (BMG LABTECH) ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all volunteers. Peripheral blood mononuclear cells (PBMCs) were isolated from blood as previously described [ 25 ]. Briefly, 20 ml of blood was collected, layered onto polymorphoprep solution (Axis-Shield, Dundee, UK) (1:1) and centrifuged for 35 min at 500× g and 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…18 Another study reported that NR4A family regulates NF-κB signalling in myeloid cells. 19 All these studies indicate that NR4A3 is involved in the regulation of ECM proteins. Furthermore, some other studies recently demonstrated NR4A3 to be involved in promoting apoptosis by inducing expression of pro-apoptotic genes in cancer cells, 20,21 while chondrocyte apoptosis is a valid target to modulate cartilage degeneration.…”
mentioning
confidence: 98%